A high-fidelity co-simulation platform for motion and control research for vehicle platooning. (2nd January 2008) - Wang, Danwei; Pham, Minhtuan
This paper presents a high-fidelity cosimulation platform to study the motion and control of a vehicle platooning system. In the study of a vehicle platooning system, the key factors include dynamic performance of all vehicles, the relative spacing and orientations of between vehicles, and the real-time implementation of a tracking controller and an autonomous vehicle in the platooning formation. This cosimulation platform integrates all these key components modelled in two softwares: ADAMS and MATLAB/SIMULINK. The advantages of ADAMS in mechanical system prototyping and those of MATLAB in advanced controller designing are exploited and combined to offer an integrated, visual and high fidelity platform for the investigation of control systems of a vehicle platooning system. The platooning dynamics is modelled in ADAMS with multiple vehicles with proper driving, steering mechanisms and sensing system to detect the distances and relative orientations between vehicles. An advanced non-linear tracking controller is developed and modelled in SIMULINK. The cosimulation of the platooning dynamics and the advanced controller is made possible by proper definition of inputs/outputs variables. This cosimulation platform is illustrated by a pair of car-like vehicles modelled in ADAMS with a non-linear controller built in SIMULINK.